2014
DOI: 10.1007/s00424-014-1553-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen restriction as challenge test reveals early high-fat-diet-induced changes in glucose and lipid metabolism

Abstract: Challenge tests stress homeostasis and may reveal deviations in health that remain masked under unchallenged conditions. Ideally, challenge tests are non-invasive and applicable in an early phase of an animal experiment. Oxygen restriction (OxR; based on ambient, mild normobaric hypoxia) is a non-invasive challenge test that measures the flexibility to adapt metabolism. Metabolic inflexibility is one of the hallmarks of the metabolic syndrome. To test whether OxR can be used to reveal early diet-induced health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…An increase in glucose oxidation is considered advantageous during OxR since the oxidation of glucose requires less oxygen than the oxidation of an equimolar amount of fat. Furthermore, an increase in glucose oxidation can prevent the increase in blood glucose levels that is often seen during OxR [ 9 ]. The analysis of blood glucose levels before and after exposure to OxR revealed a (statistical) interaction between the diet (HFpu and HFs) and oxygen level (OxR and normoxia) because HFpu and HFs responded differently to the exposure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An increase in glucose oxidation is considered advantageous during OxR since the oxidation of glucose requires less oxygen than the oxidation of an equimolar amount of fat. Furthermore, an increase in glucose oxidation can prevent the increase in blood glucose levels that is often seen during OxR [ 9 ]. The analysis of blood glucose levels before and after exposure to OxR revealed a (statistical) interaction between the diet (HFpu and HFs) and oxygen level (OxR and normoxia) because HFpu and HFs responded differently to the exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect calorimetry during OxR was performed as described [ 9 , 10 ]. For the exposure to OxR we used the same fasting regime as during the response to fasting and re-feeding (mice received 1.5 gram of feed at the start of the dark phase).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is complemented by analysis of changes in the plasma and serum proteome. Recently, for example, we have observed that changes in oxidative stress gene expression profile in WAT under different dietary conditions, is reflected by a serum marker for protein oxidation [ 112 ]. As an alternative to metabolome and proteome analysis of serum/plasma, transcriptome analysis of peripheral blood mononuclear cells (PBMC) is increasingly used [ 113 , 114 ].…”
Section: Nutrigenomics Approachesmentioning
confidence: 99%